Purely Spatial Quantum Diffusion of H Atoms in Solid H-2 at Temperatures below 1 K - Sheludiakov Sergei; Lee D. M.; Khmelenko Vladimir V.; Järvinen Jarno; Ahokas Janne; Vasiliev Sergey (AMER PHYSICAL SOC, 2025)
We report on a direct measurement of the quantum diffusion of H atoms in solid molecular hydrogen films at T = 0.7 K. We obtained a rate of pure spatial diffusion of H atoms in the H-2 films, D-d = 5(2) x 10(-17) cm(2) s(-1), which was 2 orders of magnitude faster than that obtained from H atom recombination, the quantity used in all previous work to characterize the mobility of H atoms in solid H-2. We also observed that the H-atom diffusion was significantly enhanced by injection of phonons. Our results provide the first measurement of the pure spatial diffusion rate for H atoms in solid H-2, the only solid state system beside He-3 - He-4 mixtures, where atomic diffusion does not vanish even at temperatures below 1 K.